2018
DOI: 10.1002/admi.201701637
|View full text |Cite
|
Sign up to set email alerts
|

Interference‐Enhanced Broadband Absorption of Monolayer MoS2 on Sub‐100 nm Thick SiO2/Si Substrates: Reflection and Transmission Phase Changes at Interfaces

Abstract: bandgap energy of TMDCs is in the visible range, and thus intensive research efforts have been devoted to realize highefficiency TMDC-based optoelectronic devices. [1][2][3][4][5][6][7] TMDC materials have usually been prepared on SiO 2 /Si wafers by mechanical exfoliation from the bulk or thin film deposition for physical characterization and device fabrication. After TMDC sample preparation, Raman and photoluminescence (PL) spectroscopic measurements are usually performed to identify the thickness and bandga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 32 publications
(84 reference statements)
3
18
0
Order By: Relevance
“…The surface morphology (Figure a,d) observed by AFM suggested that the area fraction of the suspended MoS 2 region near the nanodots was very small, as reported in a tip-enhanced Raman spectroscopy study . Wrinkles were detected on the MoS 2 surface, which may have formed during the wet transfer process of the relatively large MoS 2 layers (about 1 cm 2 ) . Except for the nanodot boundaries and wrinkles, the MoS 2 layers followed the surface morphology of the AuNA and AO-AuNA substrates.…”
supporting
confidence: 53%
See 2 more Smart Citations
“…The surface morphology (Figure a,d) observed by AFM suggested that the area fraction of the suspended MoS 2 region near the nanodots was very small, as reported in a tip-enhanced Raman spectroscopy study . Wrinkles were detected on the MoS 2 surface, which may have formed during the wet transfer process of the relatively large MoS 2 layers (about 1 cm 2 ) . Except for the nanodot boundaries and wrinkles, the MoS 2 layers followed the surface morphology of the AuNA and AO-AuNA substrates.…”
supporting
confidence: 53%
“…The overall PL intensity of MoS 2 /AuNA was larger than that of MoS 2 /AO-AuNA, although the PL intensity showed some spatial variation for both samples. The spatial resolution of the confocal PL measurement was about 550 nm, which is larger than the size of the nanodots. Thus, the light confinement effects near the nanodots were difficult to observe in the PL maps.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This unique material, with its special layered structure, has attracted significant interest in energy-based research. [27][28][29][30] It has many advantages: (1) extraordinary crystal, physical, chemical, electronic and photosensitive properties; [18,[31][32][33][34][35][36][37][38] (2) bandgap-adjustable properties (direct band-gap of ∼1.8 eV), potentially to be applied in electronic devices, which promotes applications containing energy conversion and storage, catalysts, and electronic devices; [31,[39][40][41][42] (3) the 2D nanostructure of MoS 2 offers a large number of active sites. These sites originate from the under-coordinated sulphur atoms at the edges, thus leading to platinum-like catalysis activity.…”
Section: Mos 2 /Graphene Composites: Key Properties For Energy Applicmentioning
confidence: 99%
“…This gives rise to two peaks in the optical absorption spectra of MoS 2 , identified as A (1.85 eV) and B (2 eV) excitons [11]. Considerable efforts have been made to study the absorption and transmission properties of these materials [40][41][42].…”
Section: Introductionmentioning
confidence: 99%